The Circuit Learning Model on Elementary Students’ Learning Outcomes - Ahmad Indra Kurniawan (Edelweiss : Journal Of Innovation In Educational Research, 2026)
The purpose of this study is to find out how the Circuit Learning Learning Model affects the learning outcomes of students of SDN 057227 Kebun Kelapa towards the grades of fourth grade students at SD Negeri 15 Sungai Liat. This type of research is a pre-experiment that only uses one class as an experimental class without a comparison class (control class) used in this type of research to determine the Effect of the Circuit Learning Learning Model , this session was attended by 25 fourth grade students. The results of the descriptive statistical analysis of the Effect of the Circuit Learning Learning Model on Student Learning Outcomes Student learning outcomes using the Circuit Learning learning model show higher results than before in Class IV of SDN 057227 Kebun Kelapa with the subject of the theme of the area where I live . The results of the inferential test analysis with the t-test formula, the calculated t value is 73.68, with a frequency of db = 25-1, and an importance level of 0.05%, so the t- table value is 17.73. So it can be concluded that Ho is rejected while Ha is accepted. This shows that the application of the circuit learning model on the learning outcomes of fourth grade students of SD Negeri 15 Sungai Liat on the theme of the area where I live is very influential.